Modeling and Simulation of Fighter Aircraft Refueling Probe Hydraulic System Using AMESim Software - Patil, Pratik; Maskar, Prabhakar; Vispute, Sanjay; Akhilesham, Ohmkar (International Journal of Computer Sciences and Engineering, 2019)
This paper presents the work carried out in the modeling and simulation of fighter aircraft refueling probe hydraulic system with Advanced Modeling Environment for performing Simulations of engineering systems (AMESim) as the basic platform. Various component models like axial piston pump, accumulator, bootstrap reservoir and actuators along with the influence of engine speed are modeled and integrated in the AMESim. Air to air refueling consists in transferring fuel from one aircraft to another during flight. The inputs for simulation are; engine speed, refueling actuation command, flaperon command, rudder command and other flight control surface command which are obtained from tests conducted on hydraulic system test rig for a fighter aircraft. Simulation is carried out to identify the system behaviour.